Light-activated nanofibre textiles exert antibacterial effects in the setting of chronic wound healing - Arenbergerova, Monika; Arenberger, Petr; Bednar, Marek; Kubat, Pavel; Mosinger, Jiri (Experimental dermatology, 2012)
The maintenance of an aseptic environment for chronic wounds is one of the most challenging tasks in the wound-healing process. Furthermore, the emergence of antibiotic-resistant bacterial strains is on the rise, rendering conventional treatments less effective. A new antibacterial material consisting of a polyurethane Tecophilic(™) nanofibre textile (NT) that was prepared by electrospinning and doped by a tetraphenylporphyrin (TPP) photosensitizer activated by visible light was tested for use in wound beds and bandages. In vitro experiments were performed to assess the antibacterial activity of the textile against three bacterial strains. Furthermore, the new textile was tested in 162 patients with chronic leg ulcers. A complete inhibition of in vitro growth of the three tested bacterial strains was observed on the surface of NTs that had been illuminated with visible light and was clinically demonstrated in 89 patients with leg ulcers. The application of the textiles resulted in a 35% decrease in wound size, as assessed via computer-aided wound tracing. Wound-related pain, which was estimated using a visual analogue scale, was reduced by 71%. The results of this trial reveal that the photoinactivation of bacteria through the photosensitized generation of short-lived, highly reactive singlet oxygen O(2) ((1) Δ(g) ) results in relatively superficial antibacterial effects in comparison with standard antiseptic treatment options. Thus, such treatment does not interfere with the normal healing process. This method therefore represents a suitable alternative to the use of topical antibiotics and antiseptics and demonstrates potentially broad applications in medicine.
Keywords: senioři; Anti-Infective Agents, Local; Wound Healing; In Vitro Techniques; Anti-Bacterial Agents; senioři nad 80 let; Bandages; porfyriny; Leg Ulcer; Light; Porphyrins; Bacterial Infections; výsledek terapie; bakteriální infekce; Middle Aged; světlo; mužské pohlaví; vředy dolních končetin; Adult; techniky in vitro; antiinfekční látky lokální; hojení ran; textilie; Pain Measurement; měření bolesti; Aged, 80 and over; ženské pohlaví; Humans; nanovlákna; Polyurethanes; antibakteriální látky; lidé středního věku; Textiles; polyurethany; Nanofibers; dospělí; obvazy; Aged; Female; Treatment Outcome; lidé; Male